Neurocognitive Dysfunction Risk Alleviation With the Use of Dexmedetomidine in Perioperative Conditions or as ICU Sedation: A Meta-Analysis - Li, Bo (Medicine (Baltimore), 2015)
Many studies have reported the beneficial effects of dexmedetomidine on postoperative neurocognitive function but overall evidence is not as clear. We examined this conundrum by meta-analyzing studies that used dexmedetomidine in perioperative conditions or as intensive care unit (ICU) sedation and utilized reliable neurocognitive assessment tests. The literature search was undertaken across several electronic databases including EBSCO, Embase, Google Scholar, Ovid SP, PubMed, Scopus, and Web of Science. Literature search was carried out across several electronic databases and relevant studies were selected after following précised inclusion criteria. Meta-analysis of risk differences (RDs) was carried out and subgroup analyses were performed. Twenty studies were selected from which data of 2612 individuals were used. Initial dexmedetomidine dose was 0.68 ± 0.27 and maintenance dose was 0.54 ± 0.32 in the trials. Dexmedetomidine treatment was associated with significantly lower risk of postoperative/postanesthesia neurocognitive dysfunction both in comparison with saline-treated controls (RD [95% confidence interval, CI]: −0.17 (−0.30, −0.04); P = 0.008) and comparators (−0.16 [−0.28, −0.04]; P = 0.009). In the subgroups analyses, however, there was no significant differences between dexmedetomidine and controls/comparators when studies with confusion assessment method for ICU only (RD: −0.10 (−0.22, 0.02); P = 0.1) or midazolam as comparator only (RD: −0.26 (−0.60, 0.07); P = 0.12) were meta-analyzed. Dexmedetomidine use in the perioperative conditions or as ICU sedation is associated with lower risk of neurocognitive dysfunction. There can be some impact of neurocognitive assessment method, drug interactions, and clinical heterogeneity on the overall outcomes of this meta-analysis.